The two curves x = y2, xy = a2 cut orthogonally at a point, then

Previous Year Papers

Download Solved Question Papers Free for Offline Practice and view Solutions Online.

Test Series

Take Zigya Full and Sectional Test Series. Time it out for real assessment and get your results instantly.

Test Yourself

Practice and master your preparation for a specific topic or chapter. Check you scores at the end of the test.
Advertisement

 Multiple Choice QuestionsMultiple Choice Questions

1011.

If :R→ R  defined by

f x = a2cos2x + b2sin2x,   x  0         = eax + b,                    x >0is continuous function,  then

 

  • b = 2loga

  • 2b = loga

  • b = log2a

  • b2 = loga


1012.

Let f(x) = ex, g(x) = sin - 1x and h(x) = f(g(x)), then

h'xhx is equal to

  • sin-1x

  • 11 - x2

  • 11 - x

  • esin-1x


1013.

If  fx = ax + a2ax, then f'a is equal to

  • 0

  • - 1

  • 1

  • a


1014.

If y = aex + be-x + c, where a, b, c are parameters, then x2y" + xy' is equal to 

  • 0

  • y

  • y'

  • y''


Advertisement
1015.

If y = acos(log (x)) + bsin (log(x)), where a, b are parameters, then xy" + xy' is equal to

  • y

  • - y

  • 2y

  • - 2y


Advertisement

1016.

The two curves x = y2, xy = a2 cut orthogonally at a point, then a2 is equal to

  • 13

  • 12

  • 1

  • 2


B.

12

We have,               x = y2      ...i 2ydydx = 1  dydx = 12yand      xy = a2      ...iixdydx + y = 0  dydx = y- xon solving equations i and ii, we get the point of interaction a2, a        m1 = dydxa2, a = 12a'and m2 = dydxa2, a = - aa2 = - 1asince, curves cut orthogonally then,m1m2 = - 112a -1a = - 1                   a2 = 12


Advertisement
1017.

If f(x) = 1 + kx - 1 - kxx, for - 1  x< 02x2 + 3x + 2,               for 0  x  1is continuous at x = 0, then k is equal to

  • - 1

  • - 2

  • - 3

  • - 4


1018.

If fx =x - 12x2 - 7x + 5, for x  1                 - 13, for x = 1, then f'1 is equal to :

  • - 19

  • - 29

  • - 13

  • 13


Advertisement
1019.

If fx = x1 + x, for x  R, then f'0 is equal to :

  • 0

  • 1

  • 2

  • 3


1020.

If u(x, y) = ylog(x) + xlog(y), then

uxuy - uxlog(x) - uylog(y) + log(x)log(y) is equal to

  • 0

  • - 1

  • 1

  • 2


Advertisement